2016
DOI: 10.1111/jgs.14050
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life at Admission Is Associated with Postdischarge Mortality, Functional Decline, and Institutionalization in Acutely Hospitalized Older Medical Patients

Abstract: Higher HRQOL at admission was associated with lower risk of mortality and functional decline 3 months after admission. In older, acutely hospitalized individuals, the EQ-5D may provide a means of risk stratification and may ultimately guide individuals, their families, and professionals in treatment decisions during hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
0
17
1
1
Order By: Relevance
“…Compared to patients with model prediction scores 0–1, the OR (95% CI) for those with scores 2–5, 6–7 and ≥8 were 1.85 (1.38–2.47, p  < 0.001), 2.30 (1.32–4.00, p  = 0.003) and 7.20 (3.33–15.50, p  < 0.001), respectively. These data were largely corroborated by Parlevliet et al, who found that health-related quality of life (HRQOL, utility based on the EuroQol-5D score) at the time of ICU admission was independently associated with risk of mortality and functional decline in a cohort of patients ≥65 years old admitted to three hospitals in the Netherlands [10], and Zeng et al who evaluated the relationship between a frailty index based on 52 discrete acute and chronic characteristics, and 300-day post-discharge mortality in a cohort of older patients admitted to a single geriatric ICU in China [11]. Finally, Bagshaw and coworkers used a validated “global” measure of frailty to demonstrate the independent effect of impaired preadmission FS on hospital and on one-year post-discharge mortality and functional outcomes [12].…”
Section: Discussionmentioning
confidence: 69%
“…Compared to patients with model prediction scores 0–1, the OR (95% CI) for those with scores 2–5, 6–7 and ≥8 were 1.85 (1.38–2.47, p  < 0.001), 2.30 (1.32–4.00, p  = 0.003) and 7.20 (3.33–15.50, p  < 0.001), respectively. These data were largely corroborated by Parlevliet et al, who found that health-related quality of life (HRQOL, utility based on the EuroQol-5D score) at the time of ICU admission was independently associated with risk of mortality and functional decline in a cohort of patients ≥65 years old admitted to three hospitals in the Netherlands [10], and Zeng et al who evaluated the relationship between a frailty index based on 52 discrete acute and chronic characteristics, and 300-day post-discharge mortality in a cohort of older patients admitted to a single geriatric ICU in China [11]. Finally, Bagshaw and coworkers used a validated “global” measure of frailty to demonstrate the independent effect of impaired preadmission FS on hospital and on one-year post-discharge mortality and functional outcomes [12].…”
Section: Discussionmentioning
confidence: 69%
“…For elderly patients hospitalized for acute illness, HRQoL is known to be an important determinant of hospital outcomes (e.g., LOS) [9,[20][21][22][23], although in dispute, other studies reported no relationship [24]. Higher baseline HRQoL is considered to have better functional reserves or ability to recover and could thus predict shorter hospital stays [10].…”
Section: Discussionmentioning
confidence: 99%
“…When used in reference to health care, QoL means health-related quality of life (HRQoL) and can be defined as a functional effect on medical conditions and/or its treatment upon a patient's physical, social, and emotional well-being [7]. In healthy and chronically ill community-dwelling elderly people, higher HRQoL is associated with longer survival and lower admission rates [8][9][10][11][12][13][14]. For the acutely hospitalized patients, HRQoL at admission predicts subsequent risk of mortality and functional decline [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pragmatic nature of this study of ‘usual care’ with assessments done by the practice nurses adds to its generalisability. The tests used have been well studied and shown to be valid, reliable and responsive across populations, for different diseases and in different clinical settings32 38 49 52 63–72. The unique aspect of this study is using these health status tests to measure multiple domains of health, including HRQoL in a primary care setting and aggregating the results to predict adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%